Impact of serum ferritin level on hepatocarcinogenesis in chronic hepatitis C patients. Issue 4 (15th May 2015) - Uchino, Koji; Tateishi, Ryosuke; Fujiwara, Naoto; Minami, Tatsuya; Sato, Masaya; Enooku, Kenichiro; Nakagawa, Hayato; Asaoka, Yoshinari; Kondo, Yuji; Yoshida, Haruhiko; Moriya, Kyoji; Shiina, Shuichiro; et al.
Abstract : Aim: To elucidate the impact of the serum ferritin level, a surrogate indicator of hepatic iron accumulation, on hepatocarcinogenesis in chronic hepatitis C patients. Methods: Serum ferritin was measured in 487 chronic hepatitis C patients without history of hepatocellular carcinoma (HCC) after excluding patients in phlebotomy, those with overt chronic gastrointestinal bleeding and those who achieved sustained virological response before enrollment. Patients were divided into four groups (G1–G4) by quartile points of serum ferritin, with sexes separated. Results: The serum ferritin level was positively correlated with total bilirubin, aspartate aminotransferase, alanine aminotransferase (ALT), γ‐glutamyltransferase, hemoglobin and AFP, and inversely correlated with prothrombin activity in both sexes. A significant difference in HCC incidence was observed only in male patients; the incidence was higher in G1 (≤80 ng/mL, n  = 54) and G4 (≥323 ng/mL, n  = 54) compared with that of G2 (81–160 ng/mL, n  = 54) and G3 (161–322 ng/mL, n  = 52). The spline curve indicating the relationship between the hazard ratio and serum ferritin level took the form of a J‐shape for male patients. In multivariate analysis, G1 and G4 showed higher incidence of HCC among men with a hazard ratio of 2.19 (95% confidence interval, 1.02–4.70; P  = 0.045) compared with G2 and G3, together with older age, lower serum albumin and ALT above the normal upper limit. Conclusion: The serum ferritin level is an independent risk factor for HCC development in male patients with chronic hepatitis C when the level is extremely high or low.